Microstructure and wear behavior of Al2024/SiFe and Al2024/SiFe/Al2O3 composites - Korkut, MH (Elsevier Sci Ltd, 2003)
The microstructure and wear properties of a new developed A12024\SiFe and A12024\SiFe/Al2O3 metal matrix composites (MMCs) produced by powder metallurgy have been investigated. Some heat treatments were applied to the extruded A12024\SiFe and A12024\SiFe\Al2O3 samples to obtain the crystallization of iron compound in the Chinese script form and to avoid the needlelike and starlike morphology. The temperature 515degreesC was obtained as the best temperature for the heat treatment, because it results in minimum liquid phase formation and yields good dissolution of iron intermetallics in all the alloys considered. Dry sliding wear tests were applied using a pin on-ring dry wear test. Pin specimens of 8 mm diameter and 12 mm in length, were machined from A12024, A12024\SiFe and A12024\SiFe\Al2O3 samples, which were rubbed against rotating steel ring (SAE 1045) at a sliding speed of 0.15-2.0 ms(-1) over the load range from 40-350 N. After dry sliding wear the debris and worn surface were studied by scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS) and X-ray diffractometry (XRD). According to EDS and XRD results, the debris for mild wear mainly consisted of ferric oxide (Fe2O3) while the debris for severe wear was composed of Al2O3, Al, alpha-Fe phases. Moreover, the addition of SiFe eutectic alloy and Al2O3 particulates increased the transition load from mild to severe wear of A12024 alloy by more than three times and decreased the coefficient of friction. The mechanism of wear does not change by the addition of SiFe eutectic alloy powders and Al2O3 particulates reinforcement. In addition, three wear regimes were seen, which are namely oxidation-induced delamination, high strain-induced delamination, and sub-surface delamination (microgroving). Nevertheless, it was seen that the transition load is completely different for matrix and particulates, but the transition from mild to severe wear forms at the same wear rate, about 4.2 x 10(-3) mm(3)m(-1) in both the matrix and the composite. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: powder metallurgy; metal matrix composites; wear